2007
DOI: 10.4049/jimmunol.178.12.7859
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Dendritic Cell Secreted Protein (FDC-SP) Regulates Germinal Center and Antibody Responses

Abstract: We previously identified follicular dendritic cell secreted protein (FDC-SP), a small secreted protein of unknown function expressed in human tonsillar germinal centers (GC). To assess potential in vivo activities of FDC-SP, transgenic mice were generated to constitutively express FDC-SP in lymphoid tissues. FDC-SP transgenic mice show relatively normal development of immune cell populations, with the exception of a small increase in mature follicular B cells, and normal lymphoid tissue architecture. Upon immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 39 publications
(45 reference statements)
0
25
1
Order By: Relevance
“…2 is a small secretory protein that was originally identified in primary follicular dendritic cells isolated from human tonsils (1) and was implicated in modulation of B cell activity (2). Recently, we have found that FDC-SP is expressed specifically in periodontal ligament and parotid gland and has molecular properties similar to those of statherin, a protein in saliva thought to function in preventing calcium precipitation (3).…”
Section: Fdc-spmentioning
confidence: 99%
“…2 is a small secretory protein that was originally identified in primary follicular dendritic cells isolated from human tonsils (1) and was implicated in modulation of B cell activity (2). Recently, we have found that FDC-SP is expressed specifically in periodontal ligament and parotid gland and has molecular properties similar to those of statherin, a protein in saliva thought to function in preventing calcium precipitation (3).…”
Section: Fdc-spmentioning
confidence: 99%
“…In a ligature-induced model of periodontitis in rats the expression of FDCSP was significantly decreased during the establishment of periodontal attachment loss, while interleukin 17 (IL-17) and the RANKL/OPG ratio were up regulated, indicating a state of acute inflammation and increased bone resorption, respectively. This suggests a possible role for FDCSP in mediating the inflammatory responses to periodontal pathogens in the JE, and ties back to the documented immunmodulatory role of FDCSP (Al-Alwan et al, 2007; Hou et al, 2014). …”
Section: Roles In the Junctional Epitheliummentioning
confidence: 61%
“…Recently, studies have also suggested that acute stimulation by FDC-SP could potentially act in concert with CXC chemokines to enhance B-cell migration, whereas chronic exposure to high levels of FDC-SP can blunt their migratory responses. 11 In the absence of chronic exposure to high levels of FDC-SP, B cells in GCs in the tonsils of IgAN patients may present enhanced migratory responses from the dark zone to the light zone, where they undergo isotype switching, and differentiation into IgA 1 plasma cells or memory cells. Consistent with this, in a previous study, we had observed enhanced IgA class switching in the tonsils of IgAN patients, which correlated with the production of IgA in tonsils (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Previous studies have reported that FDC-SP regulates GC and antibody responses. 11 More interestingly, a recent study has shown that FDC-SP controls IgA production 12 ; it is therefore possible that FDC-SP may be involved in IgA production in tonsils in individuals with IgAN. However, the mechanism by which FDC-SP may regulate production of IgA remains unclear.…”
Section: Introductionmentioning
confidence: 98%